Comparison of JET-C DD neutron rates independently predicted by the ASCOT and TRANSP Monte Carlo heating codes. (15th December 2021) - Weisen, H.; Sirén, P.; Varje, J.; JET Contributors
Abstract: Simulations of the DD neutron rates predicted by the ASCOT and TRANSP Monte Carlo heating codes for a diverse set of JET-C (JET with carbon plasma facing components) plasmas are compared. A previous study (Weisen et al 2017 Nucl. Fusion 57 076029) of this data set using TRANSP found that the predicted neutron rates systematically exceeded the measured ones by factors ranging between 1 and 2. No single explanation for the discrepancies was found at the time despite a large number of candidates, including anomalous fast ion loss mechanisms, having been examined. The results shed doubt on our ability to correctly predict neutron rates also in the deuterium–tritium plasmas expected in the JET D–T campaign (DTE2). For the study presented here the calculations are independently repeated using ASCOT with different equilibria and independent mapping of the profiles of temperature and density to the computational grid. Significant differences are observed between the results from the investigations with smaller systematic differences between neutron rates measurements and predictions for the ones using ASCOT. These are traced back not to intrinsic differences between the ASCOT and TRANSP codes, but to the differences in profiles and equilibria used. These results suggest that the discrepancies reported in reference (Weisen et al 2017 Nucl. Fusion 57 076029) do not require invoking any unidentified plasma processes responsible for the discrepancies and highlight the sensitivity of such calculations to the plasma equilibrium and the necessity of a careful mapping of the profiles of the ion and electron densities and temperatures.